2023
DOI: 10.5751/es-13594-280115
|View full text |Cite
|
Sign up to set email alerts
|

Scale, evidence, and community participation matter: lessons in effective and legitimate adaptive governance from decision making for Menindee Lakes in Australia’s Murray-Darling Basin

Abstract: Rivers and their interdependent human communities form social-ecologically complex systems that reflect basin scale functionally but are often governed by spatially mismatched governance systems. Accounting for this complexity requires flexible adaptive governance systems supported by legitimacy in decision-making processes. Meaningful community dialogue, information exchange, transparency, and scientific rigor are essential to this process. We examined failings in the adaptive governance of the Menindee Lakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The two key issues for conservation are related to the potential impacts of water level variation affecting refugia during dry times and diversity of prey. There are considerable challenges for turtles in drying river systems (Ford et al, 2023; Georges & Guarino, 2017), with turtles dependent on refugia during dry times, when analyses indicated that the diets of the three sympatric species may increasingly overlap, and reductions in prey availability may affect the survival of turtles. Rivers in the Murray–Darling Basin generally have many perennial waterholes, but the effects of river regulation and climate change are increasingly affecting the availability of water.…”
Section: Discussionmentioning
confidence: 99%
“…The two key issues for conservation are related to the potential impacts of water level variation affecting refugia during dry times and diversity of prey. There are considerable challenges for turtles in drying river systems (Ford et al, 2023; Georges & Guarino, 2017), with turtles dependent on refugia during dry times, when analyses indicated that the diets of the three sympatric species may increasingly overlap, and reductions in prey availability may affect the survival of turtles. Rivers in the Murray–Darling Basin generally have many perennial waterholes, but the effects of river regulation and climate change are increasingly affecting the availability of water.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the third sector remains on the fringes of the regional networks, and that citizens are completely excluded, suggests that this element of adaptive governance is only partially realized in the preparedness networks. This is not surprising, as high quality and inclusive participation is notoriously hard to achieve [13], while poor participation can lead to unfulfilled expectations, reducing trust in local government and exacerbating conflicts [6,36]. Likewise, Raisio et al [19] note that Finnish preparedness planning is exclusive by nature: citizens may participate in the functions of producing safety and security by assisting authorities as volunteers, but they are not included in planning.…”
Section: Discussionmentioning
confidence: 99%
“…The prescriptive nature of the Water Act, the Basin Plan, and the water resource plan accreditation requirements dictate the nature and scope of regional water plans. Water planning is a top-down, technocratic process conducted by public officials, with limited considerations of the social planning contexts or social impacts of resource allocation decisions (Alston and Whittenbury 2011, Jackson and Head 2020, Sefton et al 2020, Ford et al 2023. Many policy documents reflect this approach, defining climate "adaptation" as simply adjusting water use and management rather than any broader societal and regional adaptation.…”
Section: Water Governance Relies On Models Targets and Standards Divo...mentioning
confidence: 99%